Mixed fuel based on hydrocarbon-alcohol compositions - Єфіменко, В.В.; Ващенко, Ю.М. (Proceedings of National Aviation University (archive), 2010)
Due to oil production slowdown that is causing increasing cost of petroleum products there is a need to find alternative fuels, their production methods and usage. There are three groups of conditional fuel differentiated by origin and properties, which determine their application: petroleum fuels with additive of non oil origin components, with operation properties similar to conventional petroleum fuel; synthetic liquid fuel similar to conventional petroleum fuels; non oil fuels – all they differ considerably in physical-chemical and operation properties from traditional fuels. This article deals with mixed fuels based on ethanol and petroleum fuel. The problems of their usage and ways to improve theirs physical and chemical properties were solved by adding stabilizers. One of the main problems of using ethanol as a component that increases the octane number of motor gasoline is low physical stability of the alcohol-gasoline fuel at low temperatures. Therefore, an introduction of ethanol in gasoline required a compulsory inclusion in its composition stabilizing additives that allow to homogenate the gasoline-water-alcohol system. As stabilizers of alcohol-gasoline mixtures were studied: aliphatic alcohols of C3 - C12 row, normal and iso-structure, simple ethers and esters and their organometallic derivatives, ketones, amines, and mixtures of these compounds. Adding these compounds prevents separation of gasoline that contains alcohol, to a temperature of -40 …-23 oC.